2002
DOI: 10.1113/jphysiol.2001.013324
|View full text |Cite
|
Sign up to set email alerts
|

Contractile properties of in situ perfused skeletal muscles from rats with congestive heart failure

Abstract: We hypothesized that in congestive heart failure (CHF) slow‐twitch but not fast‐twitch muscles exhibit decreased fatigue resistance in the sense of accelerated reduction of muscle force during activity. Experiments were carried out on anaesthetized rats 6 weeks after induction of myocardial infarction or a sham operation (Sham). Animals with left ventricular end‐diastolic pressure (LVEDP) > 15 mmHg under anaesthesia were selected for the CHF group. There was no muscle atrophy in CHF. Force generation by in sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
43
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 32 publications
10
43
3
Order By: Relevance
“…Interestingly, in our hands, muscles from CHF rats develop the same maximal force as muscles from Sham rats in the absence of activity before the contractions (17). Thus increased MMP activity apparently does not prevent normal function in a muscle at the onset of exercise.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Interestingly, in our hands, muscles from CHF rats develop the same maximal force as muscles from Sham rats in the absence of activity before the contractions (17). Thus increased MMP activity apparently does not prevent normal function in a muscle at the onset of exercise.…”
Section: Discussionmentioning
confidence: 49%
“…Several long-term studies report a transition toward a faster skeletal muscle phenotype, but this seems not to be the case in short-term studies (16). However, in our rat model of CHF, atrophy and fiber type conversion do not take place (17). On the other hand, we have noted that the fast-twitch flexor digitorum brevis muscle was more fragile during dissection of single fibers in the CHF than in the Sham rat (15), and Perreault et al (21) found alterations in contractility and Ca 2ϩ handling in the fast-twitch EDL muscle in rats 6 wk after induction of heart failure.…”
Section: Discussionmentioning
confidence: 57%
“…7,9,25 Surprisingly the force decrease in CHF soleus fibers was not accompanied by any decrease in tetanic [Ca 2ϩ ] i . This is in contrast to the findings in the Sham soleus fibers as well as our previously reported observations in fast-twitch fibers of both CHF and Sham rats, where there was a clear relationship between the decrease in tetanic force and [Ca 2ϩ ] i .…”
Section: Effects Of Chf On Fatigue Developmentmentioning
confidence: 97%
“…Further characteristics of the present rat model of CHF have been reported by us previously. 9,11,21 The weight and water content of soleus and EDL muscles were not significantly different between CHF and Sham groups at any time point (supplemental Table I). Thus, CHF caused no apparent muscle atrophy or edema.…”
mentioning
confidence: 95%
“…Although muscle plasticity is well established, comparative approaches to investigate phenotypic responses in muscle typically rely upon nonphysiological adaptations such as denervation [1] or pathological processes [2] to produce a measurable effect at the molecular level. Such dramatic changes in phenotype can often prove incapacitating or fatal in vertebrates.…”
Section: Introductionmentioning
confidence: 99%